CPD Editorial - Gboyega Ogunbanjo (South African Family Practice)
This is the second issue (March/April 2008) of the new look CPD section of the South African Family Practice Journal. In each issue, 6–8 CPD articles are published in very reader-friendly formats with practical tips. The focus of this section is to present relevant articles in family practice with evidence-based information to assist clinicians with management decisions.